Discovery of novel 5-oxa-2, 6-diazaspiro[3.4]oct-6-ene derivatives as potent, selective, and orally available somatostatin receptor subtype 5 (SSTR5) antagonists for treatment of type 2 diabetes mellitus. Issue 15 (1st August 2017) - Hirose, Hideki; Yamasaki, Takeshi; Ogino, Masaki; Mizojiri, Ryo; Tamura-Okano, Yumiko; Yashiro, Hiroaki; Muraki, Yo; Nakano, Yoshihide; Sugama, Jun; Hata, Akito; Iwasaki, Shinji; Watanabe, Masanori; et al.
Graphical abstract: Abstract: Somatostatin receptor subtype 5 (SSTR5) has emerged as a novel attractive drug target for type 2 diabetes mellitus. Starting from N -benzyl azetidine derivatives1 and2 as in-house hit compounds, we explored the introduction of a carboxyl group into the terminal benzene of1 to enhance SSTR5 antagonistic activity by the combination of the substituents at the 3-position of the isoxazoline. Incorporation of a carboxyl group at the 4-position of the benzene ring resulted in a significant enhancement in potency, however, the 4-benzoic acid derivative10c exhibited moderate human ether-a-go-go related gene (hERG) inhibitory activity. A subsequent optimization study revealed that replacement of the 4-benzoic acid with an isonipecotic acid dramatically reduced hERG inhibition (5.6% inhibition at 30 μM) by eliminating π -related interaction with hERG K + channel, which resulted in the identification of 1-(2-((2, 6-diethoxy-4′-fluorobiphenyl-4-yl)methyl)-5-oxa-2, 6-diazaspiro[3.4]oct-6-en-7-yl)piperidin-4-carboxylic acid25a (hSSTR5/mSSTR5 IC50  = 9.6/57 nM). Oral administration of25a in high-fat diet fed C57BL/6J mice augmented insulin secretion in a glucose-dependent manner and lowered blood glucose concentration.